Tau pathologies mediate the association of blood pressure with cognitive impairment in adults without dementia: The CABLE study - Hu, Hao; Meng, Li; Bi, Yan‐Lin; Zhang, Wei; Xu, Wei; Shen, Xue‐Ning; Ou, Ya‐Nan; Ma, Ya‐Hui; Dong, Qiang; Tan, Lan; Yu, Jin‐Tai (Alzheimer's & dementia, 2022)
Introduction This study delineated the interrelationships among blood pressure (BP), cerebrospinal fluid (CSF) core biomarkers of Alzheimer's disease (AD), and cognition. Methods The linear regression analyses were conducted in 1546 non‐demented participants (mean age of 61.58 years, range 40 to 89 years; 40% female; average days of BP measurement, 9.10 days). Mediation analyses with 10,000 bootstrapped iterations were used to explore the mediation effects. Results A clear age‐related pattern of BP was delineated. Mid‐life hypertension (especially systolic BP), late‐life lower diastolic BP, as well as mid‐ and late‐life higher pulse pressure were associated with cognitive impairment and tau‐related biomarkers. BP variability was associated only with cognition but not with CSF biomarkers. Overall, the associations between BP and cognition were partially mediated (proportion: 11% to 30%) by tau pathologies, independently of amyloid pathology. Discussion Tau pathologies might play important roles in the relationship between BP and cognition, with significant age‐ and BP‐type dependences.